Interaction between the dominant negative mutant and the wild-type envelope proteins of Friend murine leukemia virus. - Matano, T (1994)
Interaction between the previously obtained dominant negative mutant, referred to as fcr (T. Matano, T. Odawara, M. Ohshima, H. Yoshikura, and A. Iwamoto, J. Virol. 67:2026-2033, 1993), and the wild-type envelope proteins (Env) of Friend murine leukemia virus was examined. The wild-type Env was bound to the fcr mutant Env and trapped in the endoplasmic reticulum. The virus receptor was not involved in this interaction.